Experience Reflection Modelling as a generative research method in an educational case for sustainable product design. (2014) - Turhan, Senem; Doğan, Çağla
A generative research method, namely Experience Reflection Modelling (ERM), has been developed aimed at helping students explore and reflect upon design considerations for sustainability in the idea generation phase of a design process. ERM has been integrated into a product design for sustainability project as part of the design education in the Department of Industrial Design at Middle East Technical University. This paper begins by providing an overview of the generative research approach, explaining its significance and implications for the design process. This will be followed by a presentation of the My Sustainable Mini Oven project, explaining the main design considerations (i.e., engaging design solutions, product maintenance and repair, and effective use of resources). Concurrently, it will present the tools and techniques involved in the ERM method (i.e., interviewing, three-dimensional modelling, and video recording and analysis techniques), its phases (i.e., preparation, session and analysis) and its implications for the development of sustainable design solutions. Finally, conclusions will be drawn and insights will be made into the further development of the ERM method.